Implementasi Kebijakan Pengelolaan Barang Milik Negara Berdasarkan Prinsip Hukum Islam di UIN Sultan Maulana Hasanuddin Banten - Azim, Muhamad Fadli; Tejasunarya, Jaka Laksana; Ardiani, Mila Ayu; Efriyanah, Ernah; taufik, Trisna; Polindi, Miko; Diesy, Putri (Tasyri' : Journal of Islamic Law, 2025)
This study aims to describe in detail the implementation of the State Property Management Policy (BMN) at UIN Sultan Maulana Hasanuddin Banten. The method used in this study is a qualitative descriptive method with data collection techniques through interviews, observations, and documentation related to BMN management. This study uses the policy implementation theory approach proposed by Donald Van Meter and Carl Van Horn, with six indicators as a reference. The results of the study show that the management of BMN at UIN Sultan Maulana Hasanuddin Banten is in accordance with Government Regulation Number 28 of 2020 concerning BMN/Regional Management and is in line with the implementation indicators developed by Van Meter and Van Horn. However, this study suggests that institutions review the Standard Operating Procedures (SOPs) for each type and category of BMN to improve management effectiveness. In addition, in Rector's Decree Number 180 of 2023 which regulates service rates at UIN SMH Banten, rental rates for laboratories, campus vehicles, and several other campus facilities have not been listed.